Epileptic syndrome in the clinical picture of the diseaseand the level of antibodies to GluR1 subunit of AMPA glutamate receptors in the patients with gliomas in the cerebral hemispheres of a brain - V. N. Ochkolyas; A. F. Gurchin; A. A. Skoromets; A. V. Kostyukevich (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2013)
The authors examined 92 patients with gliomas in the cerebral hemispheres. The immunoenzyme method was used for semiquantitative assay of the level of autoantibodies to GluR1 subunit of AMPA receptors of glutamate. Frequency and clinical features of symptomatic epilepsy, the reaction of AMPA receptors of glutamate depending on localization and degree of malignance and features of clinical course of the disease wereinvestigated as well. Marked increase of the level of autoantibodies to GluR1 subunit of AMPA receptors of glutamate was noticed in the patients with gliomas associated with epileptic syndrome. Maximal level of autoantibodies to GluR1 subunit of AMPA receptors of glutamate seen under the effect of the tumor on the frontal and temporal lobels.